109k views
3 votes
What is the standard form of the equation below?

What is the standard form of the equation below?-example-1
User Psyrus
by
5.2k points

1 Answer

2 votes

Solution:

we are given with the equation


x^2+y^2-2x-4y=4

This equation can be written in the standard form as below


x^2-2* x* 1+1^2+y^2-2* y * 2+2^2-1^2-2^2=4\\\\(x-1)^2+(y-2)^2-5=4\\\\(x-1)^2+(y-2)^2=5+4\\\\(x-1)^2+(y-2)^2=9\\

Hence the required equation in standrad form is
(x-1)^2+(y-2)^2=9\\

User Akhilesh Pandey
by
5.0k points